Using Active Learning Strategies to Strengthen Cultural and Linguistic Diversity Training in Communication Sciences and Disorders Programs. - O'Fallon, Maura; Garcia, Felicidad (Perspectives of the ASHA Special Interest Groups, 2023)
Purpose: Training in cultural competence is an accreditation requirement for graduate programs in communication sciences and disorders (CSD; Council on Academic Accreditation in Audiology and Speech-Language Pathology, 2020). Cultural and linguistic diversity (CLD) instruction within CSD programs and current instructional models may not provide students with effective training in this area (Hammond et al., 2009; Higby et al., 2021; Stockman et al., 2008). In this tutorial, we present active learning as an instructional approach that may provide students with stronger training in the assessment and treatment of individuals with unfamiliar cultural and linguistic backgrounds. Conclusions: Active learning emphasizes the creation of a supportive classroom environment, teaching skills rather than content, and fostering metacogni-tion in students (Bransford et al., 2000; Gooblar, 2019). We propose a three-part pedagogical model for using active learning strategies to improve clinical training in assessment and treatment of clients with CLD backgrounds. This pedagogical model encourages instructors to set the scene for learning, present a problem to solve, and build in reflection and generalization. Active learning approaches, as described in the model, are ideal for teaching clinical problem solving across populations while reflecting on one's lived experience and posi-tionality. Sample materials for readers to create their own lesson plans using the model are provided and reviewed.